Pembentukan Kompetensi Profesional Melalui Praktik Organisasi Profesi Jurnalistik: Studi Persatuan Wartawan Indonesia Mandailing Natal - Maulid Ragil Pangestu; Syaipullah Ahmad; Syafrida Hannum; Nurul Fatma Hidayah Batubara; Siti Suraya Lubis; Fitri Ani Aulia Rangkuti; Ilmi Khodijah; Nur Indah Nasution; Nur Prasanti; Rahmi Wahyuni (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah dan Komunikasi, Universitas Islam Bunga Bangsa Cirebon, 2026)
In the current era of digital media transformation, professional organizations play a decisive role in sustaining journalistic standards. This study investigates how the Indonesian Journalists Association (PWI) Mandailing Natal branch shapes the professional competencies of its members through institutional practices. Drawing on qualitative case study methodology, data were gathered through in-depth interviews with eighteen informants, participatory observation, and documentary analysis over forty days at the PWI Mandailing Natal secretariat. Thematic analysis reveals that PWI contributes to competency development through four principal mechanisms: formal training programs including Journalist Competency Tests (UKW), professional networking and knowledge exchange, journalistic ethics enforcement and mediation, and advocacy for press freedom and journalist protection. Nevertheless, the organization confronts persistent structural challenges, including limited budgetary resources, uneven member participation, a pronounced generational digital skills divide, and the accelerating pace of media industry transformation. These findings underscore the central yet constrained role of local professional associations in building journalism capacity in non-metropolitan regions. The study recommends differentiated training, formalized mentoring schemes, strengthened institutional partnerships, and supportive public policy frameworks to enhance organizational effectiveness in sustaining professional journalism.